Variations in Serum Iron Profile, in Pre and Post Hemodialysis Patients of Chronic Renal Failure - Majida Memon, Jawaid Hussain Memon, Faima Rani Memon, Aqeela Memon, Abdul Ghafoor, Salma Mumtaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the variations in iron profile in pre- and post-hemodialysis patients with chronic renal failure. Material and methods: This cross-sectional study was conducted at the physiology department with the collaboration of the urology department of Liaquat University Hospital Hyderabad, from April 2021 to September 2021. Patient of either gender with chronic kidney disease between the ages of 18- and 50-years undergoing hemodialysis were included. Blood samples were collected using serum tubes to analyze the iron profile before and after dialysis. Changes in hematological parameters were evaluated by comparing pre and post data. All data were recorded in a proforma and entered into the SPSS 26.0 version for the purpose of analysis. Results: A total of 167 patients were studied; their mean age was 43.23+12.90 years. Out of all study subjects 61.1% were males and 38.9% were females. The mean duration of dialysis was 13.40 ± 2.88 months. As per the pre- and post-serum iron profiles, the average serum iron level, serum ferritin level, and serum TIBC were statistically insignificant (p- >0.05). Conclusion: In conclusion, the iron levels before dialysis were observed to be higher than after dialysis, and the average levels of serum ferritin and total iron binding capacity (TIBC) were found to be higher after dialysis, albeit statistically insignificant. Keywords: Hemodialysis, serum iron, ferritin, TIBC